Structure of Fish Community in The Alas River of Aceh Tenggara District - Hesty Wahyuningsih (International Journal of Ecophysiology, 2021)
Research on the Community Structure of Fish on the Alas River in Babul Makmur sub-district Aceh Tenggara district was conducted from April to October 2018. The aim of this research was to analyze the structure of fish communities and to analyze physical-chemical factors related to fish community structures in the water of the Alas River in Babul Makmur sub-district Aceh Tenggara district. This research using "Purposive Sampling" method on the location based on human activities i.e the tributary of the Lawe Pakam (household waste disposal), the meeting of 2 rivers (sand dredging), the river parent (tourism), the mountain stream (free of activity). Sampling using nets. Seven species of fish obtained from the study sites were classified into 3 ordo (Cypriniformes, Perciformes, Siluriformes). The result showed that station 1 had the highest fish density at 0.3 ind / m2 for species Tor tambroides. Station 3 had the highest fish diversity index at 1.6213. Temperature, phosphate, light intensity, light penetration, dissolved oxygen and oxygen saturation had strongly correlated with fish diversity in the waters of the Alas River.